Active methodologies in the teaching and learning process of architectural design (Research, Society and Development, 2021)
This article aims to analyze the capacity of active methodologies to enhance the teaching and learning process of architectural design in the undergraduate course in Architecture and Urbanism, offered by the Federal University of Ceará. The methodology present in the research is characterized as a descriptive study, with a qualitative approach, of the experience report type, where teaching proposals are presented, especially the use of augmented reality (AR), for the students present in the discipline of architectural design and the measurement of this learning in the classroom. The results obtained show the successful use of active methodologies as learning tools, motivating the student to dedicate himself even more to the discipline when building more effective knowledge. The conclusion of the research confirms the transformative potential of these methodologies within the teaching and learning process where the teacher has the possibility to work, in the classroom, several tools that help him to approach the content, and to bring the student to the center of the discussion and reflection. Due to the restrictions caused by the Covid-19 pandemic, such as the development of classes in a virtual way, these tools are applied even more necessary in the educational sphere.